2017
DOI: 10.1103/physrevd.95.112003
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an alternative χc0(2P) candidate in e+e

Abstract: Observation of an alternative χ c0 (2P ) candidate in e + e − → J/ψDD We perform a full amplitude analysis of the process e + e − → J/ψDD, where D refers to either D 0 or D + . A new charmoniumlike state X * (3860) that decays to DD is observed with a significance of 6.5σ. Its mass is (3862 +26 −32 +40 −13 ) MeV/c 2 and width is (201 +154 −67 +88 −82 ) MeV. The J P C = 0 ++ hypothesis is favored over the 2 ++ hypothesis at the level of 2.5σ. The analysis is based on the 980 fb −1 data sample collected by the B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 53 publications
5
75
1
Order By: Relevance
“…Thus, two χ c0 (2P) candidates like X(3840) in Ref. [40] and X(3860) reported by the Belle Collaboration [45] should be excluded.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, two χ c0 (2P) candidates like X(3840) in Ref. [40] and X(3860) reported by the Belle Collaboration [45] should be excluded.…”
Section: Introductionmentioning
confidence: 98%
“…Note that χ c0 prefer to be produced with J/ψ and decay into the DD final state. While the significance of the first Belle observation was less than 5σ , the later Belle analysis using increased statistics of the full data set has confirmed the observation of χ c0 (2P) with the significance of more than 6σ [53]. In addition, Belle showed that J PC = 0 ++ is more preferable for this candidate than 2 ++ , although with low significance, 2.5σ .…”
Section: X(3915)mentioning
confidence: 70%
“…Within this picture, the first state seems too narrow, which can complicate its measurement in the experiments of Ref. [8]. What appears to be clear is that none of the J PC = 0 ++ states seems to favor a X(3915) assignment, neither by mass nor by width.…”
Section: Pos(hadron2017)113mentioning
confidence: 97%
“…Recent works favor a J PC = 2 ++ nature for the latter, which as a side effect would imply a large non-qq component for the X(3915) state [6,7]. Furthermore, a new charmonium-like state decaying to DD, called X(3860), has been recently reported by the Belle Collaboration [8], with a mass of 3862…”
Section: Introductionmentioning
confidence: 99%